Deepening democracy: challenges of governance and globalization in India - Kishwar, Madhu Purnima (Delhi, 2005)
This volume brings together essays by noted scholar-activist Madhu Purnima Kishwar on enduring issues such as rights, governance, and the impact of globalization on the average Indian citizen. The volume covers a range of issues from a glimpse of the Licence-Permit-Raid Raj as it affects the livelihood of the self-employed poor, to a critique of India's farm and economic policies. It further discusses the new divides being created by the country's language policy to the causes and possible remedies for ethnic conflicts in India. A common thread running through all essays is how most of India's contemporay problems arise out of malgovernance, the choice of inappropriate policies, and a lack of accountability in government that adversely affects the people of India, depresses their incomes, and makes it difficult for ordinary hard working citizens to earn a simple livelihood w it hout payoffs and suffering numerous humiliations. Kishwar argues that the poor need economic freedom far more urgently than the rich and builds a case for a bottom-up agenda of economic reforms. Challenging the critics of globalization, the volume demonstrates how, if India participates actively and intelligently in the WTO, this will open far-reaching opportunities for the farm sector as well as its industries. While acknowledging that the current trade regime is biased in favour of powerful industrialized nations, Kishwar points to entrenched assumptions and positions taken by those she calls the Anti-Globalization Brigade who claim that liberalization and globalization are intrinsically anti-Third World and anti-poor.
Keywords: Democracy